Designing the structure and determining the operating parameters of a microwave dehydrator for obtaining phyto-concentrates - Burdo, Oleg; Bezbakh, Igor; Kepin, Mykola; Burdo, Alla; Yevtushenko, Igor; Bahmutian, Natalya; Phylipova, Lyudmila; Kharenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is the process of obtaining phyto-concentrates using a continuous microwave dehydrator. The task addressed is associated with the concentration of food solutions in existing evaporators: product sticking to heat exchange surfaces, change in product quality, the need for additional systems for mixing, high energy consumption, inability to achieve high concentrations. The structure of a microwave dehydrator operates under periodic and continuous modes. The dehydrator's productivity has been determined depending on microwave field power, solution type, as well as product type. Wine, apple, and grape juices; coffee and echinacea extracts, as well as extracts with acetone solvent, were investigated as solutions. For water-containing products, the productivity value varied in the range of 0.28…0.32 kg/h. The dehydrator's operating modes have been defined, enabling the preservation of heat-sensitive components of the raw materials. The highest content of ascorbic acid was found in the concentrate of actinidia berries (375 mg) and bioflavonoids (18.5 mg). The concentrate of grape juice exceeds the control sample (directly squeezed juice) by 6.5 times. The high quality indicators of the product and low energy consumption of the dehydrator are attributed to the selectivity of microwave heating, which has a directed effect on polar molecules of moisture and solvent, without overheating the raw materials. The dehydrator was operated under a continuous mode, which makes it possible to increase productivity, processing quality, reduce metal consumption, and simplify its structure. The energy efficiency of the dehydrator is also based on the fact that due to its use it is possible to exclude a conventional dryer from the technological chain. A feature of the dehydrator design is the lack of need for constant operation of the vacuum pump, which ultimately reduces energy consumption. The scope of its application includes food and processing sectors, production of phyto-concentrates, functional drinks, as well as additives. Conditions of use: small businesses and farms working with heat-sensitive raw materials